Penguatan English Literacy Anak-Anak di Kampung Lembang Jaya - Jaya, William Surya; Desyana, Desyana; Crisfaniyanti, Deslita; Wahyudi, Eko; Haket, Nurfadillah; Christiono, Kaleb; Hariyanto, Oda I.B (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
English is still not seen as a need to be mastered in villages related to economic problems, so we plan to conduct English training so that local people can learn English like residents in the city. English has become a must-have skill nowadays, because English is used as a communication tool between nations, so we can understand, learn and use products from abroad.